COMPARATIVE STUDY OF KANTAKARIMUL SIDDHA DUGDHA PARISHEKA AND TRIPHALA GHRIT ASCHYOTANA IN VATAJ ABHISHYANDA W.S.R. TO ALLERGIC CONJUCTIVITIS - Shelke Madhavi Rakhamaji; Paner Paras; Dakhore Jyoti; Shinde Govind (International Journal of Applied Ayurved Research, 2017)
Background:Highly polluted environment, has an effect on lifestyle. Simple allergic con-junctivitis is one of the outcomes of this changing lifestyle, food habits, and polluted envi-ronment.Simple allergic conjunctivitis is a common form of ophthalmic problem prevalence 5-22% and recurrence found in 41 – 62% of the cases. The eye and eye lids are common sites for allergic reactions. It is hypersensitivity reaction to specific airborne antigens. Abhishyanda is one of sarvgata roga mentioned in sushruta samhita. vataj abhishyanda.Vataj abhishyanda is characterised by Toda (pricking sensation), sangharsha ( f b sensation ), ashruta (watery discharge), alpa shopha (mild chemosis ), vishushka bhava ( feeling of dryness). Vataj abhishyanda is a clinical condition which can be co-related with allergic conjunctivitis. Patients were selected from OPD & IPD of shalakya dept of Eknath Ayurved Rugnalaya, Shevgaon and were selected randomly divided into two groups.10 pa-tients of trial group were treated with Kantakari mul siddha dugdha parisheka.10 patients of control group were treated with Triphala ghrit aschyotan. Duration of treatment was 28 days. Results-final assement was done at 28th day. Both treatments are effective in vataj abhishyanda but kantakari mul siddha dugdha parisheka is more significant. Conclusion: Kantakari mul siddha dugdha parisheka were found more effective than triphala ghrit aschyotana in vataj abhishyanda (Allergic conjucticitis)